A natureza jurídica dos dispute boards nos contratos administrativos - Negrini Neto, João (2025)
This study addresses the role of dispute boards – conflict prevention and resolution committees – as an innovative and efficient tool for resolving disputes that arise during the execution of administrative contracts. The absence of specific federal regulation for these committees does not prevent their growing use, which is encouraged by the General Law of Public Procurement and Contracts and recognized in longterm and high-complexity public procurement models. The analysis begins with a historical and doctrinal overview of the institution, presenting its origin, dissemination, and regulation in municipal legislation, as well as its main characteristics and differences from other alternative dispute resolution methods. The study explores the main distinctive aspects of dispute boards compared to mediation and negotiation, highlighting that, unlike other methods, committees can issue recommendations or decisions that, although not binding as in arbitration, carry the authority of the contractual text. While arbitration has a definitive decision-making character – with the effect of res judicata – dispute boards provide decisions that can later be reviewed in judicial or arbitral instances, offering an additional layer of security and control, especially relevant in public contracts. Additionally, the study examines the legal structure of dispute boards, revealing how these committees perform administrative functions delegated by the public administration, linking them to the specific legal regime of administrative acts. This characteristic allows these committees' decisions to be subject to judicial or arbitral review, with their actions embedded in a conflict resolution system that includes, sequentially, negotiation, mediation, arbitration, and, eventually, judicial review. Finally, the study proposes the possibility of harmonizing the legal regime of dispute boards with that of arbitration, considering the adoption requirements of each institution and the case law that admits arbitration in disputes involving public administration, as long as the decisions do not affect the State's inalienable public interests. The study concludes that, although a general regulation would be desirable to ensure greater predictability and uniformity, local regulation and encouragement by the General Law of Public Procurement already represent significant progress and enable its use by public administration. Dispute boards, alongside arbitration, have established themselves as viable and effective alternatives for resolving conflicts in administrative contracts, reflecting the modernization of public administration and the pursuit of greater efficiency in public procurement